Dirac exciton–polariton condensates in photonic crystal gratings - Sigurðsson Helgi; Nguyen Hai Chau; Nguyen Hai Son (Nanophotonics)
Bound states in the continuum have recently been utilized in photonic crystal gratings to achieve strong coupling and ultralow threshold condensation of exciton–polariton quasiparticles with atypical Dirac-like features in their dispersion relation. Here, we develop the single- and many-body theory of these new effective relativistic polaritonic modes and describe their mean-field condensation dynamics facilitated by the interplay between protection from the radiative continuum and negative-mass optical trapping. Our theory accounts for tunable grating parameters giving full control over the diffractive coupling properties between guided polaritons and the radiative continuum, unexplored for polariton condensates. In particular, we discover stable cyclical condensate solutions mimicking a driven-dissipative analog of the zitterbewegung effect characterized by coherent superposition of ballistic and trapped polariton waves. We clarify important distinctions between the polariton nearfield and farfield explaining recent experiments on the emission characteristics of these long lived nonlinear Dirac polaritons.